(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The procedure for the administrative misconduct action is different because it has a preliminary stage, prior to the receipt of the initial petition. The defendant manifests itself by means of a prior defense, which, if accepted, will lead to the rejection of the action. This article will deal with the rejection of the action for lack of sufficient evidence (just cause), for the lack of individualization of the defendants’ conduct and for the absence of demonstration of the subjective element of the type.